Khartoum. L’invenzione di una capitale (1898-1910) - Marina D’Errico (Bollettino della Società Geografica Italiana)
The city of Khartoum, the capital of present-day Sudan, strategically located at the crossroads of the crossings of the African continent, along the north-south and east-west routes, was rebuilt ex novo by the British, at the turn of the 19th-20th century. Founded in 1820 in the context of Turkish-Egyptian Egypt, it grew rapidly in the central decades of the 1800s, it was then sacked and partially destroyed after 1885 during the years of the Mahdist revolt. Following the British re-occupation of Sudan, the city was rebuilt on the basis of an urban plan devised by an excellent team. The project represented a real laboratory, in which the theme of the urban and progressive utopia of doctors and urban planners was confronted with the white man’s civilizing mission, but the interpretation of the design of the city appears anything but easy to read. From a careful analysis of the papers developed and of the literature, it is possible to advance the hypothesis that the matrix of the plan is of a military nature and that the urban structure, based on a series of diagonal road axes, has been designed to guarantee the safety of the settlers with respect to local populations through a spatial organization that, although developed horizontally (unlike other colonial cities located in an elevated position), offered the maximum visibility and facilitated the operations of intervention by the British army.